On SAH – Ideal of BH – Algebra - Abed, Alaa Saleh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The aim of this investigation is to present the idea of  SAH â€“ ideal , closed SAH â€“ ideal and closed SAH â€“ ideal with respect to an element ,  and s-  of BH â€“ algebra .We detail and show  theorems which regulate the relationship between these ideas and provide some examples in BH â€“ algebra .